mRNA-specific translational regulation in yeast - Erguden, Bengu (Tech Science Press, 2019)
The expression of a gene is governed at various levels, from transcriptional to translational level. The translational control is widely used to regulate gene expression, especially when a rapid, local, and selective control over protein synthesis is required. The present review describes instructive examples of translational regulation in yeast, together with regulatory elements within mRNAs. The review also outlines the important contributions of mRNA-binding proteins that act in harmony with several translational elements to generate appropriate translational signals and responses.
Keywords: Translational regulation; Saccharomyces cerevisiae; Global control of translation; mRNA regulatory elements; mRNA-binding proteins